PENGARUH MODAL USAHA, LAMA USAHA, JAM KERJA DAN PEMASARAN ONLINE TERHADAP PENDAPATAN PEDAGANG PAKAIAN PASAR BLAURAN KLANDASAN: Rahma, Dewi Sartika Program Studi S1 Manajemen, STIE Madani Balikpapan Email : sartikadewi@stiemadani.ac.id - Sartika, Dewi (JURNAL AKUNTANSI DAN MANAJEMEN MADANI, 2024)
Klandasan II Market or commonly called Blauran Klandasan Market is one of the markets located in Balikpapan City. In this market, various kinds of goods are sold, including in the field of fashion or apparel specifically located on the entire second floor. At clothing traders in this market, they complain about the decrease in income, causing economic instability. The purpose of this study is to find out what factors can affect the income of clothing traders in the Blauran Klandasan Market. Several factors can affect a trader's income, including business capital, length of business, working hours, and online marketing. This study uses primary data and secondary data. The method used is quantitative. The results showed that there was a significant positive effect between working capital on merchant income, there was a significant positive effect between the length of business on merchant income, there was a significant positive effect between working hours on merchant income, and there was no significant influence between online marketing on merchant income. The results of the F and regression tests found that there was an effect of 41.7% between business capital, length of business, working hours, and online marketing together on merchant income and the remaining 58.3% is influenced by other variables.